Return Literature: A Reading on The Meanings and Connotations of The Title - Ramazan Ömer (Şarkiyat Mecmuası)
Modern Palestinian literature has undergone fundamental transformations through three main phases: the pre-Nakba (Catastrophe) period, the post-Nakba period, and the post-Oslo Accords period. These phases have shaped the structure and themes of Palestinian literature. Resistance literature has been associated with or derived from various concepts such as “Nakba Literature,” “Fighter Literature,” “Diaspora Literature,” and “Literature of Return.” These terms reflect the diversity of issues addressed by Palestinian literature, necessitating a clear distinction between them to define their meanings and roles. This study examines “Literature of Return” as an independent literary concept within Palestinian resistance literature, distinguishing it from other related notions to provide a more precise definition. This study explores the fundamental characteristics of “Literature of Return” and its role in emphasizing the right to return as an integral part of Palestinian national identity. This study adopts the literary analysis method by examining various texts and investigating works related to the term “Literature of Return.” In addition, it addresses the different contexts and associations of this term. Additionally, it highlights “Literature of Return” as an independent literary genre that focuses exclusively on the issue of returning to the homeland, setting it apart from other literary currents related to the Palestinian cause. One of the key findings of this study is that “Literature of Return” is a distinct and independent literary genre, differing from “Literature of the Returnees” and “Migrant/Diaspora Literature,” which establishes it as a unique and autonomous category within Palestinian literature.